(untitled) (LACCEI, 2024)
The research work uses the Kanban tool, which is an opportunity to generate continuous flow and improve the flow of materials and increase productivity, where they eliminate waste such as reducing waiting to serve the internal client (productive system), transfers unnecessary mobile equipment, overproduction and work-in-process inventories. And align processes, standardize routes among others in a food company. Through the pull system, efficiency was improved in internal transfer operations of materials and finished products, from the input logistics warehouses to the distribution warehouses, considering the quantities necessary to minimize stocks, supported by production planning. the master plan that will indicate the quantities of SKUs and the materials plan or MRP I for the supply of materials